Hydranencephaly in Neonates - Jeng-Dau Tsai; Huang-Tsung Kuo; I-Ching Chou (Elsevier, 2008)
Hydranencephaly is characterized by severe dysgenesis of the cerebral hemispheres, with relative preservation of the thalamus, cerebellum and brainstem. Modern neurological imaging techniques have demonstrated that the affected regions are usually localized within the territories of the middle cerebral arteries. Evoked potentials have confirmed the imaging findings. This article reports on two neonates with hydranencephaly who presented with normal appearance. Neurological images were characterized by marked reduction of the total brain cortex, which was replaced by fluid. Evoked potentials demonstrated preserved auditory evoked potentials but a total absence of visual evoked potentials. These diagnostic techniques provided efficient and precise information concerning the extent of intracranial dysgenesis.